Successful professional reviews for civil engineers - Steels, H. Macdonald (Thomas Telford, 2006)
Explains the purposes behind the Institution of Civil Engineers' Professional Reviews for all classes and grades of qualifying membership. The author examines the constituent parts of the review process and how they fit together to ensure a holistic outcome.
Previous ed.: 1997.
Keywords: Civil engineering -- Practice -- Great Britain.; Civil engineering -- Standards -- Great Britain.; elektronické knihy; electronic books